Penerapan Metode Dempster Shafer Pada Sistem Pakar Diagnosis Penyakit Kejiwaan - Raharisti, Nur Arifah; Atina, Vihi; Hartanti, Dwi (Infotek: Jurnal Informatika dan Teknologi, 2024)
Mental illness is a condition where the sufferer has problems related to mental, physical, developmental and social disorders which can hinder the life process in interacting with the environment or other people properly. Limited mental health service facilities and a lack of understanding about mental illness often cause sufferers to ignore their condition, which can worsen their illness. From this problem, so it is necessary to have an expert system that can diagnose mental illness. This research aims to produce the design and development of an expert system for diagnosing mental illness so that it is able to overcome existing limitations and reduce the level of risk of mental illness. The Dempster Shafer method is used to assess the level of confidence in decision making regarding a disease by paying attention to each selected symptom value. This research produces an expert system that includes 28 symptom data and 5 disease data providing output in the form of diagnosis results, symptoms, the highest percentage of a disease and appropriate advice. This system has been tested with 15 test data, with an accuracy success rate of 86.6%.